Analisis Loyalitas Pelanggan di PT Nutrifood, Kotamadya Bogor - Samsudin Samsudin (Institut Ilmu Sosial dan Manajemen STIAMI, 2018)
Entering the era of milenimum to 3, each company including PT Nutrifood faced with the burden of a very tight competition, given the flourishing number of similar companies. To be able to still exist, developed and developing, and come out as winners in the era of global competition, every company is required to have comparative and competitive advantages are high. One of them is a strategy on how to keep your customer or customers remain loyal and faithful to the products they offer. Dynamic market conditions, manufacturers incentive to issue new products, and combined with the trend of people who like to try, then it creates loyalty is a very heavy task, because consumers like to try new things. PT Nutrifood feel this phenomenon and there are fears a time when consumers turn to similar products produced by other companies. Moreover, intense competition, often consumers switch to other products from other companies, either because of considerations selection of better quality, prices are relatively cheaper, the quality of the packaging is better, tastes better, and also just try switching curiosity or curious and want to try other products. This study uses quantitative methods. The study population was a customer PT Nutrifood, Bogor municipality, which amounted to 77 people with acendential sampling method, the sampling is based on the fact that they happen to appear. Each respondent was given 10 questions to answer gradation using a Likert scale, while research conducted around the month of March 2018. From this research it is known that customer loyalty PT Nutrifood categorized as good, which is indicated by a score average achieved penapsiran figure of 3.89. With the results of these studies are expected to PT Nutrifood minimal customer loyalty can be maintained, even need to be improved better by improving customer satisfaction through improved quality of service.